Risk and protective factors for coronavirus disease 2019 (COVID-19) in allergic rhinitis patients: a national survey in China - Yang, Xiaozhe; Sima, Yutong; Zhao, Jinming; Zhang, Jing; Wang, Xiangdong; Zhang, Luo (Frontiers in Allergy, 2024)
BackgroundSeveral epidemiological studies have shown that allergic rhinitis (AR) patients are more susceptible to coronavirus disease 2019 (COVID-19).ObjectiveWe aim to investigate the risk factors for COVID-19 in AR patients.MethodsA retrospective nationwide cohort study was conducted based on a questionnaire survey in China. The baseline characteristics, region of residence, smoking and drinking status, comorbidities, vaccination status and previous infection information were obtained. Allergen test results, the SARS-CoV-2 nucleic acid test, and antigen detection results were collected. Information on AR and comorbid medication use pre-SARS-CoV-2 infection was also collected. Binary logistic regression and analysis of covariance (different adjusted models) were conducted.ResultsIn all, 830 AR patients were included; 627 patients (75.54%) were infected with SARS-CoV-2. AR comorbid with allergic conjunctivitis (AC) was a protective factor [OR: 0.525 (95% CI = 0.296–0.929), P = 0.027] against SARS-CoV-2 infection, while AR comorbid with food allergy was a risk factor [OR: 6.404 (95% CI = 1.349–30.402), P = 0.0195]. Although fewer patients received four doses of the vaccine, the results showed a significant protective effect against SARS-CoV-2 infection in AR patients [OR: 0.093 (95% CI = 0.025–0.348), P = 0.0004]. Underweight was a protective factor against COVID-19 [OR: 0.287 (95% CI = 0.147–0.562), P = 0.0003] after full multivariable adjustment. Overweight was associated with a 2.071-fold higher risk for COVID-19 compared with normal weight [(95% CI = 1.045–4.105), P = 0.0370]. Additionally, house dust mite (HDM)-specific allergies were also protective against COVID-19 [OR: 0.537 (95% CI = 0.290–0.996), P = 0.0484].ConclusionsThis study revealed underlying protective and risk factors, which might be used to improve the management of AR and COVID-19.